Proceedings of the 12th International Workshop on Automating TEST Case Design, Selection, and Evaluation 2021
DOI: 10.1145/3472672.3473952
|View full text |Cite
|
Sign up to set email alerts
|

Using an agent-based approach for robust automated testing of computer games

Abstract: Modern computer games typically have a huge interaction spaces and non-deterministic environments. Automation in testing can provide a vital boost in development and it further improves the overall software's reliability and efficiency. Moreover, layout and game logic may regularly change during development or consecutive releases which makes it difficult to test because the usage of the system continuously changes. To deal with the latter, tests also need to be robust. Unfortunately, existing game testing app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The iv4xr framework tries to fill this role. The advantage of a more programming-based approach is that we have much more control on the test agent behavior, and we have also shown that a BDI test agent is robust against development time changes [15].…”
Section: Related Workmentioning
confidence: 89%
See 2 more Smart Citations
“…The iv4xr framework tries to fill this role. The advantage of a more programming-based approach is that we have much more control on the test agent behavior, and we have also shown that a BDI test agent is robust against development time changes [15].…”
Section: Related Workmentioning
confidence: 89%
“…For more combinators, including conditional and repetition, see [13], with which even a test algorithm can be expressed, e.g. when the exact sequence of sub-tasks is not known upfront [15].…”
Section: Formulating a Testing Task: Goal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works on explorative agents for ABD have developed more sophisticated agents that are closer to human testers [1] than the more traditional rule/search based systems [19,3,16]. The incorporation of learning into these agents has become a key tool in allowing them to explore more effectively.…”
Section: Bug Identificationmentioning
confidence: 99%
“…We believe this is due to the problem's inherent difficulty, but also at least in part due to the difficulty of the experimental set up, as can be seen in [11]. In addition, the lack of a shared platform, or comparative baselines for testing ABD approaches has led to a somewhat fractured literature and to difficulties in evaluating and comparing performances, as can be seen on the exploration side of ABD [2,4,16,19].…”
Section: Introductionmentioning
confidence: 99%